The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.15666/aeer/1604_47534771
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Physiological Responses of Stevia (Stevia Rebaudiana Bertoni) to Various Priming Treatments Under Drought Stress

Abstract: Poor germination capacity of stevia is a major problem in its cultivation. Moreover, drought stress is one of the most major environmental constraints, which influences seed germination and early seedling growth of many crops. The aim of this research was to evaluate the impact of seed priming with salicylic acid (SA), zinc (Zn) and iron (Fe) on some germination parameters and physiological attributes of stevia seedlings under drought stress induced by polyethylene glycol (PEG) 6000 (0, -3, -6 and -9 bars). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Proline, non-enzymatic antioxidants response, is known to act as an osmolyte /osmoprotectant agent under drought or salinity stress (Lehmann et al, 2010). The osmolyte has an important role in the scavenging free radicals, osmotic pressure adjustment, stabilizing sub-cellular structures and storing carbon and nitrogen (Gorzi et al, 2018). The results of current study concluded that a significant increase in the free proline content and activity of CAT and SOD enzymes under salt stress especially in 150 mM NaCl level.…”
Section: Discussionmentioning
confidence: 58%
“…Proline, non-enzymatic antioxidants response, is known to act as an osmolyte /osmoprotectant agent under drought or salinity stress (Lehmann et al, 2010). The osmolyte has an important role in the scavenging free radicals, osmotic pressure adjustment, stabilizing sub-cellular structures and storing carbon and nitrogen (Gorzi et al, 2018). The results of current study concluded that a significant increase in the free proline content and activity of CAT and SOD enzymes under salt stress especially in 150 mM NaCl level.…”
Section: Discussionmentioning
confidence: 58%
“…A significant increment of all these parameters has been observed from 0.5 to 4% of PEG 6000 concentration. Few previous reports have enlightened the enhancement of growth and antioxidants after exposure of S. rebaudiana to PEG 6000 while others disagree on the growth and secondary metabolites increase and ultimately susceptibility to water deficiency in the environment [18][19][20][21][22][23][24]. Hajihashemi and Ehsanpour [21] documented an increase in antioxidant activities of S. rebaudiana under rising levels of PEG 6000 concentration, i.e., 0, 2, 4, 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Hajihashemi et al [20] also elucidated enhancement of antioxidant activities in the callus of S. rebaudiana treated with PEG 6000 (0 and 4%) along with different growth regulators. Additionally, Gorzi et al [24] documented improved seedling growth and uprising antioxidant capacity upon exposure to PEG 6000 stress. These reports coincide with our study and prove the drought tolerance in S. rebaudiana on increasing PEG 6000 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hal tersebut sebagaimana penelitian Matsushima dan Sakagami (2013) pada biji padi yang menunjukkan bahwa hydropriming dapat mempersingkat waktu perkecambahan secara signifikan, meningkatkan bobot kering pucuk, bobot kering akar, panjang pucuk, dan laju pemanjangan pucuk secara signifikan dibandingkan dengan kontrol (tanpa perlakuan) pada berbagai tingkat kelembaban tanah. Gorzi Gorzi et al (2018) menemukan bahwa priming dengan kombinasi 1 mM SA, 0.5% Fe, 0.5% Zn pada biji Stevia (Stevia rebaudiana) menunjukkan nilai persentase perkecambahan, laju perkecambahan, panjang semaian, indeks vigor semaian, klorofil, aktivitas CAT, dan aktivitas POD maksimum dibandingkan dengan perlakuan lain dan kontrol pada semua tingkat stres kekeringan (0, -3, -6, dan -9 bar). Dampak positif dari priming tersebut juga ditunjukkan pada penelitian Pinheiro et al (2018) yaitu meningkatnya persentase perkecambahan dengan 50 ppm GA 3 serta meningkatnya indeks kecepatan perkecambahan pada biji sorghum genotip BRS-330 dan L-20, pertumbuhan akar, dan keseimbangan rasio akar terhadap pucuk pada genotip BRS-330 dengan 100 ppm GA 3 pada kondisi stres kekeringan.…”
Section: Pendahuluanunclassified